Highly Dynamic Changes in the Activity and Regulation of Macroautophagy in Hearts Subjected to Increased Proteotoxic Stress - Pan, Bo; Lewno, Megan T.; Wu, Penglong; Wang, Xuejun (Frontiers in Physiology, 2019)
Macroautophagy (referred to as autophagy hereafter) plays an important role in the quality control of cellular proteins and organelles. Transcription Factor EB (TFEB) globally activates the expression of genes in the autophagic-lysosomal pathway (ALP) to replenish lysosomes and ALP machineries. We previously reported that myocardial TFEB signaling was impaired in advanced cardiac proteinopathy; however, myocardial ALP status and TFEB activity at earlier stages of cardiac proteinopathy remain uncharacterized. Here a stable line of CryABR120G transgenic (R120G) and non-transgenic (NTG) littermate mice with cardiomyocyte-restricted overexpression of CryABR120G were used at 1, 3 and 6 months of age. At 1 month when no cardiac phenotypes other than aberrant protein aggregation are discernible, R120G mice displayed a 5-fold increase in myocardial LC3-II flux. Interestingly, the LC3-II flux increase co-existed with increases in mTOR complex 1 (mTORC1) activities as well as cytoplasmic, but not nuclear, TFEB proteins. This increase in cytoplasmic TFEB proteins occurred without any discernible alteration in TFEB activity as reflected by unchanged mRNA levels of representative TFEB target genes (Mcoln1, M6pr, Sqstm1, Vps18 and Uvrag). At 3 months of age when hypertrophy and diastolic malfunction start to develop, the LC3-II flux remained significantly increased but to a lesser degree (2-fold) than at 1 month. The LC3-II flux increase was associated with decreased mTORC1 activities and with increased nuclear TFEB proteins and TFEB activities. At 6 months of age when congestive heart failure is apparent in R120G mice, both LC3-II flux and TFEB activities were severely suppressed, while mTORC1 activity increased. We conclude that changes in both autophagy and TFEB signaling are highly dynamic during the progression of cardiac proteinopathy. Increases in autophagy occur before increases in TFEB activities but both increase in the compensatory stage of cardiac proteinopathy. Once congestive heart failure develops, both autophagy and TFEB signaling become impaired. Our results suggest that TFEB signaling is regulated by both mTORC1-dependent and -independent mechanisms in hearts subjected to increased proteotoxic stress. For therapeutic exploration, it will be important to test the effect of TFEB stimulation at the early, intermediate and late stages of cardiac proteinopathy.